Metabólitos fecais de glicocorticoides e detecção de Neospora caninum em quatis (Nasua nasua) cativos - Morgado, Thais Oliveira (2018)
Chronic stress monitoring plays a key role in management of wild animals in captivity, since the number of captive animals has been increasing dramatically and a large number of Brazilians zoos are responsible for conservation programs and reproduction of threatened species. Although coati (Nasua nasua) is a widely distributed and relatively common species, is still little studied. The purpose of this study was to evaluate the health of coatis kept in captivity at Zoo of Federal University of Mato Grosso, as by means of a pathogenic agent, Neospora caninum, as to provide an initial tool to evaluate the welfare and management conditions of this species. Thus, the adrenocorticotrophic hormone (ACTH) challenge test was used to validate the noninvasive method of evaluating the adrenal activity for the quantification of fecal metabolites of glucocorticoids (GCMs) in coatis measured by the radioimmunoassay (RIA). On the other hand, the neosporosis with a little elucidated wild cycle, the investigated in captive coatis without studies was performed, considered as the main cause of reproductive loss in bovines and neuromuscular diseases in dogs. Thus, by molecular techniques was first described the presence of N. caninum in necropsied coatis’ organs. From such results, with the validation of the RIA technique for GCMs of this species is possible to determine the stress level of these animals and, with the report of N. caninum in coatis, to enable greater clarification of the role of procyonides in the epidemiology of neosporosis.